(untitled) (Academicia Globe: Inderscience Research, 2021)
The proposed article analyzes the problem of the formation of social competence in children of primary school age. In the process of studying the theoretical material on this issue, we clarified the concept, social competence, identified the psychological and pedagogical conditions for the formation of social competence among younger schoolchildren, where the program for the implementation of conditions was followed.